2020
DOI: 10.1055/a-1236-3007
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of convolutional neural network-based artificial intelligence in diagnosis of gastrointestinal lesions based on endoscopic images: A systematic review and meta-analysis

Abstract: Background and study aims Recently, a growing body of evidence has been amassed on evaluation of artificial intelligence (AI) known as deep learning in computer-aided diagnosis of gastrointestinal lesions by means of convolutional neural networks (CNN). We conducted this meta-analysis to study pooled rates of performance for CNN-based AI in diagnosis of gastrointestinal neoplasia from endoscopic images. Methods Multiple databases were searched (from inception to November 2019) and studies that repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…In this meta‐analysis, the application of AI in the diagnosis of OSCC comprehensively achieved pooled AUROC of 97%, pooled sensitivity of 95% and pooled specificity of 92%. These results are in keeping with those of previous meta‐analyses, 9 , 10 , 64 , 65 , 66 in which AI showed good performance in the diagnosis of OSCC, BE‐related or gastric adenocarcinoma and colorectal lesions.…”
Section: Discussionsupporting
confidence: 91%
“…In this meta‐analysis, the application of AI in the diagnosis of OSCC comprehensively achieved pooled AUROC of 97%, pooled sensitivity of 95% and pooled specificity of 92%. These results are in keeping with those of previous meta‐analyses, 9 , 10 , 64 , 65 , 66 in which AI showed good performance in the diagnosis of OSCC, BE‐related or gastric adenocarcinoma and colorectal lesions.…”
Section: Discussionsupporting
confidence: 91%
“…In recent years, CAD tools are providing an interpretable universal method for endoscopic diagnosis, virtually eliminating variability among observers. Recent metaanalyses [72][73][74][75] confirmed the potential of AI to increase the diagnostic yield and reduce underdiagnosis of upper GI neoplastic lesions, often performing comparably or better than expert endoscopists. However, most studies on CAD tools were retrospective and tested the diagnostic yield of AI on endoscopic images rather than during live EGDS.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to insufficient data they could not compare the effectiveness of computer‐aided algorithms with that of endoscopic physicians. In another meta‐analysis 36 the metrics of pooled sensitivity, specificity, PLR, NLR, DOR and AUROC for AI could not be obtained due to significant heterogeneity of the included studies and those based on SVM were excluded. One study 34 concluded that the use of NBI resulted in a higher AUROC of the AI models than the use of WLI in the diagnosis of ESCC, while in our study we found no statistical difference in AUROC between the use of WLI and NBI.…”
Section: Discussionmentioning
confidence: 99%